Single-Item Happiness Measure Features Adequate Validity Among Adolescents - Lukoševičiūtė, Justė; Gariepy, Geneviève; Mabelis, Judith; Gaspar, Tania; Joffė-Luinienė, Roza; Šmigelskas, Kastytis (Frontiers in Psychology, 2022)
BACKGROUND. Happiness is becoming increasingly relevant in recent research, including adolescents. Many studies are using the single-item measure for adolescent happiness, however, its validity is not well known. We aimed to examine the validity of this measure among adolescents in three countries from distinct European regions – Eastern (Lithuania), Southern (Portugal), and Western (Scotland). METHODS. The analysis included data from Health Behaviour in School-aged Children (HBSC) study from 3 countries and 3 last surveys (2009/10, 2013/14, 2017/18). The total sample comprised 47,439 schoolchildren. For validity, the indicators reflecting subjective health, life satisfaction, quality of life, well-being, social support, health complaints, bullying, and self-directed violence were assessed. The calculations were conducted in the total sample and by gender, age, survey year, and country. RESULTS. The different indicators of concurrent and convergent validity revealed consistent correlations with happiness, with better well-being, health, and subjective perceptions being related to higher happiness. Meanwhile, health complaints, bullying behaviors and self-directed violence were related to lower happiness. The subgroup differences were consistent across gender, age groups, countries, and survey rounds. The extent of differences was more expressed among girls. CONCLUSION. The single item for adolescent happiness measurement features a consistent pattern of validity concerning indicators of concurrent and convergent validity. Higher self-reported happiness is associated with better mental and physical health and well-being, and less expressed negative factors (complaints, bullying, and self-directed violence). In addition, among girls the correlations tend to be stronger than boys.